(untitled) (Anclajes, 2015)
Two dissimilar strategies of construction of the self organize the autobiographical writings of Victoria and Silvina Ocampo; one pursues the reconstruction of memory, the other prefers the opacity of memory. On the one hand, the line of interpretation I develop from Inventions of the memory (2006) —the autobiography in verse of Silvina Ocampo, based on childhood memories— centers around the relation between memory writing, misremembering, and the problem of infancy (Agamben). On the other hand, my reading of El Archipiélago[The Archipelago] (Sur, 1979) —the first volume of Victoria Ocampo’s autobiography, corresponding her childhood— aims at showing the way in which the author relies on the possibility of clearly narrating the memory time, using the strategies of classical autobiography (Lejeune).